Comparison of Individual Radiosensitivity to γ-Rays and Carbon Ions - Shim, Grace; Normil, Marie Delna; Testard, Isabelle; Hempel, William M.; Ricoul, Michelle; Sabatier, Laure (Frontiers in Oncology, 2016)
Carbon ions are an up-and-coming ion species currently being used in charged particle radiotherapy. As it is well established that there are considerable inter-individual differences in radiosensitivity in the general population that can significantly influence clinical outcomes of radiotherapy, we evaluate the degree of these differences in the context of carbon ion therapy compared to conventional radiotherapy. In this study, we evaluate individual radiosensitivity following exposure to carbon-13 ions or γ-rays in peripheral blood lymphocytes of healthy individuals based on the frequency of ionizing radiation (IR)-induced DNA double strand breaks (DSBs) that either misrepaired or was left unrepaired to form chromosomal aberrations (CAs) (simply referred to here as DSBs for brevity). Levels of DSBs were estimated from the scoring of CAs visualized with telomere/centromere-fluorescence in situ hybridization (TC-FISH). We examine radiosensitivity at the dose of 2 Gy, a routinely administered dose during fractionated radiotherapy, and determined that a wide range of DSBs were induced by the given dose among healthy individuals, with highly radiosensitive individuals harboring more IR-induced breaks in the genome than radioresistant individuals following exposure to the same dose. Furthermore, we determined the relative effectiveness of carbon irradiation in comparison to γ-irradiation in the induction of DSBs at each studied dose (iso-dose effect), a quality we term ‘relative dose effect’ (RDE). This ratio is advantageous as it allows for simple comparison of dose response curves. At 2 Gy, carbon irradiation was 3 times more effective in inducing DSBs compared to γ-irradiation (RDE of 3); these results were confirmed using a second cytogenetic technique, multicolor-FISH. We also analyze radiosensitivity at other doses (0.2 to 15 Gy), to represent hypo- and hyper-fractionation doses, and determined that RDE is dose-dependent: high ratios at low doses, and approaching 1 at high doses. These results could have clinical implications as IR-induced DNA damage and the ensuing CAs and genomic instability can have significant cellular consequences that could potentially have profound implications for long-term human health after IR exposure, such as the emergence of secondary cancers and other pathobiological conditions after radiotherapy.